How Does "Stay Home" Transform a House? The Route Map of a Research - EKE, ARMAĞAN SEÇİL MELİKOĞLU; ÖZBEK, DERYA ADIGÜZEL; USTA, GÜLAY; SALTIK, ÖZGE ILIK; Özerenler, Sedef Sav; DEMİR, ELİF GELMEZ; EVLİYAOĞLU, FURKAN (Konya Technical Univ, Fac Architecture & Design, 2022)
COVID-19 pandemic caused transformation by influencing the physical and psycho-social status of houses, and by introducing different functions and needs which led to or will lead to changes in individuals' expectations from their houses. Drawing on this idea, this study allows for the detection of such changes through examination and for the consideration of future house arrangements, housing designs and their production by identifying the usage possibilities of existing houses. The research design is structured in three main steps. First step is the literature part that draws the conceptual framework of the study. Second step includes survey technique with use of panel design as a quantitative research method. In the research, third step has built with semi-structured interview to be deepen analyzing of the results of the quantitative part. The findings reached through this study have the potential to lead future house arrangements as well as housing production and design which are also significant in terms of innovative and creative housing designs studied within disciplines such as interior architecture and architecture. Sample of the research is the city of Istanbul which is first of the most affected cities from COVID-19 pandemic. Selecting a big and multi-component metropolis like Istanbul as research area for residential spaces brought different difficulties in the application processes of research methods while allowing the multidimensional examination of the subject. The research design proposed by this study possess the quality of a guiding sample for future scientific studies.
Keywords: Covid-19 Pandemic; Housing; Research Design; Quantitative Research; Qualitative Research